1987
DOI: 10.1002/ajmg.1320280420
|View full text |Cite
|
Sign up to set email alerts
|

Pathological confirmation of cystic fibrosis in the fetus following prenatal diagnosis

Abstract: Prenatal diagnosis of cystic fibrosis is presently based on the determination of microvillar enzyme activities in the amniotic fluid. However, there seems to be no accurate means for confirming the diagnosis of the aborted fetus. During the past year we performed pathological and histopathological examinations on 7 fetuses diagnosed in the second trimester of pregnancy to be affected by cystic fibrosis and compared them with 4 control age-matched fetuses. Glycol-methacrylate-embedded 2-3-mu thick sections of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 14 publications
(8 reference statements)
1
43
0
1
Order By: Relevance
“…Cells along the distal secreting ducts of the glands generate the H 2 O 2 -producing enzyme dual oxidase (Duox) (36). This is probably why the initial histological abnormality of CF fetuses occurs in submucosal glands (1,2), because in the absence of SCN Ϫ from the serous cells, unconsumed H 2 O 2 would be expected to irritate and harm the secreting glands, leading to inflammation and injuries. Duox activity indirectly stimulates mucin expression by epithelial cells (37); and mucin has a protective effect in that it scavenges ROS, including H 2 O 2 (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells along the distal secreting ducts of the glands generate the H 2 O 2 -producing enzyme dual oxidase (Duox) (36). This is probably why the initial histological abnormality of CF fetuses occurs in submucosal glands (1,2), because in the absence of SCN Ϫ from the serous cells, unconsumed H 2 O 2 would be expected to irritate and harm the secreting glands, leading to inflammation and injuries. Duox activity indirectly stimulates mucin expression by epithelial cells (37); and mucin has a protective effect in that it scavenges ROS, including H 2 O 2 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Lung injuries cause Ϸ90% of the morbidity and mortality of CF patients. The lungs of CF newborns exhibit no obvious anatomic abnormality, except the presence of somewhat thicker mucus secretion in submucosal glands and possible dilation of the gland ducts (1,2). Thick secretion may plug the ducts, predisposing them to infection.…”
mentioning
confidence: 99%
“…Airway disease in CF is characterised by mucus plugging, chronic infection and an excessive inflammatory response, leading to peripheral airway changes in the first few months of life [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. The characteristic airway abnormalities are bronchiectasis, thickening of the airway wall and mucus plugging [97,103,107,[120][121][122][123][124][125][126], as shown in figure 5.…”
Section: Airway Imaging In Cystic Fibrosismentioning
confidence: 99%
“…Recent studies have shown that CFTR can function as a Cl channel activated by protein kinase A phosphorylation and nucleoside triphosphates (9,10); mutations in CFTR cause cystic fibrosis (CF) (1 1, 12). Some complications of CF, including meconium ileus and pancreatic duct obstruction, occur before birth (13)(14)(15), suggesting the defective gene product is expressed in epithelia of these tissues prenatally. Therefore, the developmental regulation of CFTR gene expression in the human may bear directly on the timing of the disease onset.…”
Section: Introductionmentioning
confidence: 99%